Unusual toxic accident caused by Calosoma alternans, Fabricius 1792 (Coleoptera: Carabidae) in a Venezuelan patient - Gil-Zambrano, Gisselle C.; Reyes-Lugo, Rafael M.; Salvi, Iván; RodrÃguez-Acosta, Alexis (Revista Cubana de Medicina Tropical, 2021)
Coleopteran insects can produce toxic substances containing multiple components which have so far not been properly described. To report an unusual case of intoxication by excretion from Calosoma alternans Fabricius 1792 (Coleoptera: Carabidae) in a Venezuelan patient from a periurban neighborhood near the mesothermal raining forest. The toxic activity caused a clinical status characterized by digestive symptoms such as nausea, vomiting, epigastralgia, an increase in bowel movements and probable kidney inflammation with intense pain in both lumbar regions, which did not correspond to the classic dermal damage. In conclusion, a unique case is presented of intoxication by a coleopteran species, with a clinical description not previously reported.